Creating inclusive environments in cell biology by casual mentoring. Issue 9 (September 2022) - De Lora, Jacqueline A.; Hinton Jr., Antentor; Termini, Christina M.
Abstract : Informal mentoring affects the development of cell biologists by providing essential career, scientific, and educational guidance to mentees. In this piece, we discuss the importance of formally recognizing casual mentorship to encourage this crucial form of mentorship that contributes to the advancement of an inclusive cell biology community.